Improving the Quality of Smooth Anchovy Nugget (Stolephorus sp) with the Addition of Sajiku Flour - Nurainy Kaliky (Faculty of Fisheries and Marine, Universitas Riau, 2023)
Anchovies (Stolephorus sp) are fish that have important economic value even though they are small. This fish is rich in nutritional content and has a savory and delicious taste when processed into food. This fish is very liked by various groups even though it has small in size and without bones. This anchovy contains lots of calcium, protein, and minerals such as phosphorus and iron that are very useful for increasing the intelligence of children and toddlers, as well as for preventing osteoporosis in pregnant women and the elderly as well as helping in the growth of bones and teeth in infants, toddlers, and children. To improve the quality of anchovy nuggets, it is necessary to add certain binders to improve the taste of anchovy nuggets. This study aims to improve the quality of anchovy nuggets by adding a binder in the form of sajiku flour and adding to the economic value of refined anchovy so that it is more attractive to the public. There were 3 treatments and 2 repetitions. The treatments were A. Anchovies; A1 = using carrots, A2 = without carrots, and treatment B (my flour concentration); B1=100g, B2= 200g. Moreover, Treatment C (cooking temperature); C = 65ºC - 85ºC for 30 minutes. From the results of the study, it can be seen that the water content, protein content, and fat content did not show any significant effect